2014
DOI: 10.1128/jcm.03448-13
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Nontypeable Haemophilus influenzae Strains Colonizing Australian Aboriginal and Non-Aboriginal Children

Abstract: e Nontypeable Haemophilus influenzae (NTHI) strains are responsible for respiratory-related infections which cause a significant burden of disease in Australian children. We previously identified a disparity in NTHI culture-defined carriage rates between Aboriginal and non-Aboriginal children (42% versus 11%). The aim of this study was to use molecular techniques to accurately determine the true NTHI carriage rates (excluding other culture-identical Haemophilus spp.) and assess whether the NTHI strain diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…Although H. haemolyticus has, on rare occasion, been isolated from invasive infections (6), several lines of evidence indicate that the pathogenicity of H. haemolyticus is much reduced compared with H. influenzae. While up to 20% of presumptive H. influenzae nasopharyngeal isolates can be identified as H. haemolyticus by molecular characterization (7)(8)(9), H. haemolyticus is rarely cultured from middle ear fluid (10,11), supporting the view that H. haemolyticus, in contrast to NTHi, is a respiratory commensal infrequently associated with otitis media. Reinvestigation of presumptive H. influenzae isolates, cultured from lower respiratory tract samples from cystic fibrosis patients (12) or from unselected clinical samples submitted to the laboratory on suspicion of lower respiratory tract infection (13), detected that Ͻ1% were misidentified strains, further supporting a minor pathogenic role for H. haemolyticus.…”
mentioning
confidence: 82%
“…Although H. haemolyticus has, on rare occasion, been isolated from invasive infections (6), several lines of evidence indicate that the pathogenicity of H. haemolyticus is much reduced compared with H. influenzae. While up to 20% of presumptive H. influenzae nasopharyngeal isolates can be identified as H. haemolyticus by molecular characterization (7)(8)(9), H. haemolyticus is rarely cultured from middle ear fluid (10,11), supporting the view that H. haemolyticus, in contrast to NTHi, is a respiratory commensal infrequently associated with otitis media. Reinvestigation of presumptive H. influenzae isolates, cultured from lower respiratory tract samples from cystic fibrosis patients (12) or from unselected clinical samples submitted to the laboratory on suspicion of lower respiratory tract infection (13), detected that Ͻ1% were misidentified strains, further supporting a minor pathogenic role for H. haemolyticus.…”
mentioning
confidence: 82%
“…Indigenous women are known to have higher rates of preterm delivery than nonindigenous women (13.7 vs 7.9%), but the number of preterm births in the NTHi group (83%) exceeded predictions based on indigenous origin. Indigenous Australian children are known to have high respiratory carriage rates with NTHi related to overcrowded living conditions . A predisposition to obstetric NTHi infection among indigenous mothers has not to our knowledge been previously reported.…”
Section: Discussionmentioning
confidence: 80%
“…In the Kalgoorlie studies, NTHi carriage rates among the Aboriginal (Study 3) and non-Aboriginal (Study 4) children were 36.3 % (183/504) and 9.4 % (98/1045), respectively [14]. In Study 1, 84 different PRTs were identified among 2179 NTHi isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Day 12–21 if perforation.(469)551(569)73(13)3Kalgoorlie (WA) Otitis Media Research Project. Prospective Aboriginal cohort [12, 14]1999–2005100(36.3 %)1 wk to 24 mAges 1–3, 6–8 wks, then months 4, 6, 12, 18, 24.(193)231(346)65(28)4Kalgoorlie (WA) Otitis Media Research Project. Prospective non-Aboriginal cohort [12, 14]1999–2005180(9.4 %)1 wk to 24 mAges 1–3, 6–8 wks, then months 4, 6, 12, 18, 24.(102)109(192)37(34)

RCT randomised-controlled trial, AOM acute otitis media, NP nasopharyngeal, PRT PCR-ribotype, NT Northern Territory, WA Western Australia

a A single isolate of each PRT from each swab

b All families provided written informed consent for their child’s participation

…”
Section: Methodsmentioning
confidence: 99%